Pesantren Education and Its Contribution to Developing Religious Values in Kudus Community - Utama, Ihsan Cahya; Akbar, Rofiq Faudy (Al-Qalam Institue, 2023)
This study aims to determine the Islamic boarding school education model around Kudus. This study is based on knowledge of experience and community perceptions of life in the environment around the Islamic boarding school. It explores the contribution of Islamic boarding schools in shaping the character of the Kudus community. This type of research is field research, which is included in qualitative research. Namely, researchers go into the field to obtain data. Data collection techniques include observation, interview, and documentation. The subjects of this study were the caretakers and managers of Islamic boarding schools, as well as several student and community leaders in Islamic boarding schools around Kudus. Data analysis techniques include data collection, reduction, presentation, conclusion, and verification. The study results indicate that the Islamic boarding school education model around Kudus consists of three educational models, namely the Salafiyah Islamic boarding school model, the Khalafiyah Islamic boarding school model and the comprehensive Islamic boarding school model. The perception of the Kudus community on Islamic boarding schools consists of two perceptions: positive and negative. Moreover, Islamic boarding schools contribute to shaping the religious character of the people around Kudus. The findings are expected to contribute to academic knowledge for the community and provide references for other Islamic boarding schools to continue to strive to provide broad benefits to the community.